Physiological and performance responses to a preseason altitude-training camp in elite team-sport athletes - McLean, B. D.; Buttifant, D. C.; Gore, C. J.; White, K.; Liess, K.; Kemp, J. G. (International Journal of Sports Physiology and Performance, 2013)
Purpose: Little research has been done on the physiological and performance effects of altitude training on team-sport athletes. Therefore, this study examined changes in 2000-m time-trial running performance (TT), hemoglobin mass (Hbmass), and intramuscular carnosine content of elite Australian Football (AF) players after a preseason altitude camp. Methods: Thirty elite AF players completed 19 days of living and training at either moderate altitude (~2130 m; ALT, n = 21) or sea level (CON, n = 9). TT performance and Hbmass were assessed preintervention (PRE) and postintervention (POST1) in both groups and at 4 wk after returning to sea level (POST2) in ALT only. Results: Improvement in TT performance after altitude was likely 1.5% (± 4.8-90%CL) greater in ALT than in CON, with an individual responsiveness of 0.8%. Improvements in TT were maintained at POST2 in ALT. Hbmass after altitude was very likely increased in ALT compared with CON (2.8% ± 3.5%), with an individual responsiveness of 1.3%. Hbmass returned to baseline at POST2. Intramuscular carnosine did not change in either gastrocnemius or soleus from PRE to POST1. Conclusions: A preseason altitude camp improved TT performance and Hbmass in elite AF players to a magnitude similar to that demonstrated by elite endurance athletes undertaking altitude training. The individual responsiveness of both TT and Hbmass was approximately half the group mean effect, indicating that most players gained benefit. The maintenance of running performance for 4 wk, despite Hbmass returning to baseline, suggests that altitude training is a valuable preparation for AF players leading into the competitive season.